On translating Francesco Guicciardini’s political writings - Alison Brown (Laboratoire Italien)
In addition to the problems facing all translators – how closely should the translation follow the original and how up-to-date should it be –, Guicciardini presents special problems through his avant-guard use of Italian to discuss the concepts of classical republicanism and through his demotic use of colloquialisms. To ignore them or to adjust them to fit accepted political concepts is to ignore the radicalism that underlies his homely metaphors, which – I argue – provide a novel, flexible and non-normative vocabulary of power.